Social Media's Usefulness for the Digital Generation - Euis Nurul Bahriyah; Euis Heryati; Iin Laki; Mohamad Sudi; Mashudi Hariyanto (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2023)
The purpose of this study is to characterize the internet generation's experiences in assessing social media's utility. This generation has profited from its heavy reliance on social media. Five members of the internet generation who actively use social media in their daily lives are the topic of this study. This study uses interpretive phenomenological analysis techniques in conjunction with a phenomenological methodology. In-depth interviews were used to gather data, which was then categorized using the research respondents' testimonies. The research participants reported that social network usage is a highly common habit among the internet generation's daily activities. Studies reveal that the generation born after the internet values social networks for information sharing, engagement, participation, decentralization, and accountability.